Peran Organisasi Islam Modern Dalam Perjuangan Sosial - Vita Setiyani; Syahda Tiara Putri; Linda Widia Ningsih; Karlenia Putri Solihah; Zahra Fauziana; Muhammad Azrul Amirullah (CV. ITTC INDONESIA, 2025)
Islamic organizations in the current digital and global era are not only focused on religious aspects but also actively involved in social issues, such as education, health, welfare, and human rights advocacy. This role is crucial because modern Islamic organizations often serve as a bridge between Islamic values and current social challenges, as well as assisting communities experiencing problems such as discrimination, poverty, or climate change. The capacity of modern Islamic organizations in social struggles can be strengthened through creative collaboration methods. This study has a novel qualitative descriptive approach that focuses on Islamic organizations in Indonesia. This research differs from previous studies that have focused on religious aspects or Islamic organizations globally. Instead, this study focuses on the local dynamics of modern Islamic organizations, which have unique characteristics in social struggles. This study also positions the role of organizations as agents of comprehensive social change in the modern era. This study uses a library research method, namely research conducted by examining, reading, and reviewing various literature sources relevant to the theme of the Role of Islamic Organizations in Social Struggle. The results of the discussion provide information that modern Islamic organizations have a big impact on Islamic boarding school education by using the methods they have.